299 Sentinel lymph-node mapping with indocyanine green in endometrial cancer: detection rate and anatomical sites. (4th December 2020) - Gedgaudaite, Migle; Sukovas, Arturas; Bartusevicius, Arnoldas; Paskauskas, Saulius; Vaitkiene, Daiva; Nadisauskiene, Ruta Jolanta; Gaurilcikas, Adrius
Abstract : Introduction/Background: Lymph-node status is one of the prognostic factors related to the survival of patients with endometrial cancer (EC). However, systemic pelvic lymphonodectomy (PLN) is related to increased perioperative morbidity. A number of studies using different techniques have demonstrated the sentinel lymph-node biopsy (SLB) could be a better alternative to PLN in different patient groups. With evidence still lacking, SLB is considered an experimental method by major professional organisations like European Society of Gynaecologic Oncology. The aim of this study was to evaluate the adherence of the SLB procedure in a center with no previous experience of SLB in EC. Methodology: Prospective interventional study was performed in Lithuanian University of Health Sciences Hospital, Centre of Oncogynaecology in the period of 2018 March and 2020 July. 96 patients with histologically confirmed endometrioid endometrial carcinoma were included into the study. Indocyanine green (ICG) dye was used to map sentinel lymph-nodes using previously described technique. PLN was performed after SLB procedure for intermediate and high-risk patients. Results: Detection rate, timing and anatomical sites The overall SL detection rate was 87.5% (bilateral in 63.5% (61/96), unilateral in additional 24.0% (23/96) of patients). The median time for the detection of the 1st SL was 35 minutes after injection of ICG (range 13–140 min), and 45 minutes (range 25–115 min) for the 2nd (contralateral) one. The median number of SL removed was 2 (range 1–8). The most frequent sites for SLs were right external iliac area (31.0%), left external iliac area (24.2%), right internal iliac area (11.9%) and left obturator fossa (11.3%). 4.8% of SL mapped in paraaortic region. SL metastasis rate: Lymph node metastasis were found in 6 (6.3%) patients and 4 (4.4%) of them were detected by SLB. The sensitivity of SLB was 66.7% and negative predictive value 97.4%. SLB has moderate – strong agreement with PLN (kappa coefficient 0.787, p < 0.001). SL mapping failures: SL mapping failed in 12.5% (12/96) of the patients. The factors that might be associated with mapping failure was age (73 vs. 64.5 vs. 62.8, p=0.005) and present extragenital pathology (100% vs. 60.9% vs. 57.4%, p=0.019). Conclusion: With the overall detection rate of 87.2% (63.5% bilateral and 24.0% - unilateral) we find SLB ICG procedure feasible. Most frequently SLs were detected in the external iliac region. Age and extragenital pathology are the statistically significant factors associated with the failure of SLB procedure.